Study of Corrosion Behavior of Mg–Gd-Based Soluble Magnesium Alloys - Qinghua Wang; Zhiquan Huang; Yanchun Zhu; Ling Qin; Jingfeng Zou; Lifeng Ma (Metals)
The corrosion behavior of soluble Mg–Gd-based alloys was systematically investigated by analyzing two key aspects: environmental factors and microstructural characteristics. Environmental influences were evaluated using immersion weight loss tests under varying Cl− concentrations and temperature conditions. From a microstructural perspective, the study examined the impact of different initial microstructural morphologies on corrosion performance. The second-phase compound Mg5Gd, formed in alloys prepared via melting, was subjected to both immersion weight loss and electrochemical testing. The results demonstrated that corrosion rates increased with higher Cl− concentrations and elevated temperatures, albeit in a nonlinear manner. Notably, significant effects on corrosion rates were observed in the Cl−concentration range of 1% to 3% and at temperatures between 75 °C and 100 °C. Additionally, the dissolution rate of the alloy increased markedly from 8.37 mg/cm2/h in the as-cast state to 43.85 mg/cm2/h following extrusion combined with perforation deformation. Microstructural analysis revealed that the extrusion process disrupted the coarse, reticulated second-phase structure observed in the as-cast state, thereby diminishing its corrosion-inhibiting properties. Electrochemical testing further confirmed that the Mg5Gd second phase, formed through the incorporation of the rare-earth element Gd, exhibited high electrochemical activity.